Daoist Philosophy, English Studies, and Mental Well-Being in the Digital Age: A Comparative Analysis of Ancient Wisdom and Contemporary Society - Pasupuleti Venkata Ramana, M. Ravichand, Dr. Narendra Kumar Hetcherla, Dr. Gousia Sultana, Dr. K. K. Sunalini (Journal of Daoist Studies, 2026)
Life in the digital age is marked by constant connectivity, rapid information exchange, and an unprecedented dependence on technology. While these developments have reshaped education, communication, and cultural interaction, they have also introduced new concerns related to emotional fatigue, digital distraction, anxiety, and the gradual erosion of meaningful human engagement. Such developments raise an important question: can ancient philosophical traditions still offer practical insight into the psychological realities of contemporary society? Daoist philosophy provides a compelling perspective because it approaches well-being not through control or constant achievement but through balance, naturalness, and harmony with the rhythms of life. Viewed from this perspective, the digital world is more than a technological environment; it is also a cultural space that influences thought, relationships, and personal identity. This paper reconsiders classical Daoist ideas—including Dao, Wu Wei, and Ziran—alongside contemporary discussions of mental well-being and explores how English studies contribute to interpreting these philosophical traditions through literature, language, and cultural criticism. Rather than treating Daoism as a historical belief system detached from modern experience, the discussion places it within current debates surrounding digital culture, emotional resilience, and human flourishing. The paper adopts a qualitative conceptual approach based on classical Daoist writings together with established scholarship in philosophy, literary studies, and mental health research. Through comparative interpretation, it argues that Daoist philosophy complements contemporary understandings of psychological well-being by encouraging mindful technology use, moderation, self-awareness, and healthier relationships with both the digital environment and the natural world. Bringing together ancient wisdom and contemporary scholarship, the study demonstrates that Daoist thought continues to offer meaningful intellectual resources for understanding the cultural and psychological challenges of the digital age while supporting more balanced and sustainable ways of living.